2021
DOI: 10.3390/en14175547
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Feasibility of Implementing Shower Heat Exchangers in Residential Buildings Based on Users’ Energy Saving Preferences

Abstract: In Poland, domestic hot water is heated mainly using fossil fuel energy sources. Such an approach results in the depletion of natural resources, pollution of the atmosphere and, consequently, irreversible changes to the climate. In response to this problem, this research identified the factors that most determine energy savings for heating water in residential buildings, as well as those that affect the choice of an alternative energy source. Additionally, the possibility of implementing shower heat exchangers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 63 publications
0
17
0
1
Order By: Relevance
“…This article focused on overcoming potential issues such as a lack of awareness by kitchen owners of the availability of heat recovery and its benefits. A lack of awareness and access to information has also been identified as an issue for the implementation of heat recovery systems for showers by domestic users [30]. From a technological perspective, the necessity to access a part of the drainpipe with an approximately 2 m vertical drop can constrain the installation of a heat exchanger, as can the existence of obstacles between the drainpipe and the boiler.…”
Section: Discussion Of Heat Recovery Application In Kitchensmentioning
confidence: 99%
See 2 more Smart Citations
“…This article focused on overcoming potential issues such as a lack of awareness by kitchen owners of the availability of heat recovery and its benefits. A lack of awareness and access to information has also been identified as an issue for the implementation of heat recovery systems for showers by domestic users [30]. From a technological perspective, the necessity to access a part of the drainpipe with an approximately 2 m vertical drop can constrain the installation of a heat exchanger, as can the existence of obstacles between the drainpipe and the boiler.…”
Section: Discussion Of Heat Recovery Application In Kitchensmentioning
confidence: 99%
“…The heat recovery system considered here uses a tube-in-tube heat exchanger and hence represents a kind of direct and passive heat recovery without the need for a heat pump. This and similar kinds of heat exchangers are typically used for shower water heat recovery, for which they have been studied and installed in domestic and commercial settings across the UK and Europe [20,21,[27][28][29][30]. In 2020, the installation of a heat recovery system was completed at a case study restaurant at the Penrhyn Castle tourist attraction in Wales, UK, initiated and overseen by the authors as part of the D ŵr Uisce INTERREG project, and was proven to be effective at recovering heat from kitchen drain water [15,16,31,32].…”
Section: Drain Water Heat Recovery Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that further changes in domestic hot water consumption will affect the value of peak consumption and the irregularity coefficient will increase. A survey presented in the paper [59] showed that "the perspective of environmental protection is not a sufficient motivator to save energy for heating domestic hot water" and therefore only the water and energy price model can drive further changes.…”
Section: Hot Water Consumption-standard Methodsmentioning
confidence: 99%
“…An online questionnaire was prepared in Google Form in Polish (research conducted in Poland) and English (research conducted in other seven countries) and was sent to the respondents in 2019. A similar test method was chosen, for example, by [68,69]. The questionnaire consisted of 10 questions: 4 general and 6 concerning the possibilities of saving water and rainwater and greywater systems (Figure 2).…”
Section: Survey Researchmentioning
confidence: 99%